Evaluasi Penerapan Green Campus pada Pemeringkatan UI GreenMetric World University Rangkings di Universitas Islam Negeri Walisongo Semarang - Falakh, Fajrul (Environmental Science Program, Ivet University, 2020)
Universitas Islam Negeri Walisongo Semarang has participated in the Green Campus ranking program organized by the UI GreenMetric World University Rankings in 2019 and 2020. There are six (6) categories in the UI GreenMetric standard which were assessed, namely: Setting and Infrastructure (SI), Energy and Climate Change (EC), Waste (WS), Water (WR), Transportation (TR) and Research and Education (ED). In 2019 and 2020 the Universitas Islam Negeri Walisongo Semarang was ranked 384 in the World with a total of 912 University participants worldwide. This achievement was obtained Universitas Islam Negeri Walisongo Semarang received a total score of 5,625 in the assessment in 2020. The Energy and Climate Change (EC) indicator managed to get the highest total score process compared to other indicators (23 %), While the Water Indicator (TR) received the lowest score by only getting a score percentage of 8%. Program sustainability needs to be accelerated by making specific policies that are in line with sustainable development and can be followed up with measurable programs so that they can increase the ranking in the following years.